A fractured body: James Blair begins disestablishing the Church of England in Virginia, 1690-1785 - Burton, Kevin D. (Kansas State University, 2017)
This thesis examines the development of freedom of religion in Virginia focusing on the Anglican Church in the century preceding the Constitutional Convention (May 25 to September 17, 1787). There are three main arguments in this study. First, I maintain that commissary James Blair’s actions set the Anglican Church in Virginia on a unique trajectory that favored local control. He did this despite the hierarchical structure of the Church of England that encouraged uniformity. He gained strong influence in Virginia, used his power to weaken governors and clergy, along with their ties to imperial Britain. At the same time, he empowered vestries and local control. His actions set the Anglican Church on a path different from that of the Church in other colonies. Importantly for the path of the Anglican Church in Virginia, he established and was the first president of the College of William and Mary. Second, I assert that the College of William and Mary was responsible for further developing a unique Anglican Church in Virginia. The college provided an education for future leaders, allowing the colony to develop a clergy that had spent little or no time in England. In turn, the clergy became increasingly supportive of local power, and had a diminishing connection to England. Third, I maintain that the development of a unique Anglican Church in Virginia created a culture in which Anglicans there were more receptive of the First Great Awakening (1730s-1760s), and were supportive of the American Revolution, and religious freedom. In order to demonstrate these three points, I will argue that from Blair through the American Revolution, the Church of England in Virginia followed a unique path that was essential for securing religious freedom in Virginia, and the eventual United States.
Keywords: Blair; University of Virginia; Church of England; Virginia